Analyzing Slang in Social Media - Ita Rosvita; Maria Celine Tumbel; Yusniati N. Sabata; Abdul Rabbi Arrasul (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
The purpose of this research was to determine the types of slang and slang that were most used by UMLB students of English education, Eight semesters in social media. This is descriptive qualitative research. This research was conducted by non-participatory observation which is observing social media Facebook and WhatsApp. This research is also done with the documentation of screenshots. Participants of slang users in this research were twenty seven eighth-semester students of English Education Program at UMLB. The result of this research show that there were six types of slang used by the students, those were fresh and creative, flippant, imitative, acronym, clipping, and abbreviation. The number of slang found by the researcher is 74 slangs. 18 slangs for fresh and creative, 11 slangs for flippant, 6 slangs for imitative, 5 slangs for acronym, 13 slangs for clipping, and 21 slangs for abbreviation. Therefore based on the data, abbreviation is the most used slang or often used by UMLB students of English education, eight semesters in social media